2017
DOI: 10.1186/s12917-017-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

Salivary pH, calcium, phosphorus and selected enzymes in healthy dogs: a pilot study

Abstract: BackgroundSaliva in dogs, as in humans, is a complex fluid secreted by different salivary glands in the oral cavity to protect the oral mucosa and teeth. The use of saliva as a substitute for blood in diagnosing and prognosticating disease in humans is widely accepted. Salivary biochemistry has also been used as a marker for periodontal disease in humans. No studies have as yet investigated the relation between salivary biochemistry and periodontal disease in dogs, however; neither has the salivary composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
13
2
4
Order By: Relevance
“…The salivary urea test strip method is based on changes in the test‐pad colors due to the release of hydroxyl ions (and subsequent alteration of the pH) during the cleavage reaction of the salivary urea nitrogen by urease present in the test pad. A recent study found that the average pH of canine saliva was 7.93, whereas, in humans, the salivary pH ranges from 6.2 to 7.6, with a mean pH of 6.7 . In our study, the median salivary pH was 8.7, which was more alkaline than previously reported, although this was only assessed in 18/33 dogs due to insufficient volumes of saliva being obtained.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The salivary urea test strip method is based on changes in the test‐pad colors due to the release of hydroxyl ions (and subsequent alteration of the pH) during the cleavage reaction of the salivary urea nitrogen by urease present in the test pad. A recent study found that the average pH of canine saliva was 7.93, whereas, in humans, the salivary pH ranges from 6.2 to 7.6, with a mean pH of 6.7 . In our study, the median salivary pH was 8.7, which was more alkaline than previously reported, although this was only assessed in 18/33 dogs due to insufficient volumes of saliva being obtained.…”
Section: Discussioncontrasting
confidence: 68%
“…A recent study found that the average pH of canine saliva was 7.93, whereas, in humans, the salivary pH ranges from 6.2 to 7.6, with a mean pH of 6.7 . In our study, the median salivary pH was 8.7, which was more alkaline than previously reported, although this was only assessed in 18/33 dogs due to insufficient volumes of saliva being obtained. This higher salivary pH could falsely increase the salivary test strip value since the test pad detects alterations in the pH, although the results were corrected using the control pad according to the manufacturer's instructions, which should have accounted for these differences.…”
Section: Discussioncontrasting
confidence: 68%
“…Lysozyme, secreted mainly by polymorphonuclear cells and leukocytes, has antibacterial properties interacting with microbial growth and metabolism [68,69]. It is reported how the concentration of this enzyme increases following inflammatory processes or bacterial infections, while it decreases in response to acute stress because of the immunosuppressive effects of glucocorticoid secretion that inhibits the functioning of monocytes and macrophages [36,38].…”
Section: Discussionmentioning
confidence: 99%
“…The pH range in saliva may vary from 6 to 8.6, depending on the state of the organism [16,17]. The ability to maintain an alkaline pH in saliva is important because saliva in the oral cavity plays an antibacterial role and swallowing saliva can also compensate for acidic pH in the stomach, especially in cases of reflux disease [18]. Several reports show that the pH of colon or gastric mucosa can reach 8–8.2 and, in particular, the alkaline contents of gastric mucosa serve to protect the stomach from the acidic contents [19,20].…”
Section: Resultsmentioning
confidence: 99%